Demystifying the dark side of AI in business - Dadwal, Sumesh Singh 1973-; Goyal, Shikha; Kumar, Pawan 1980-; Verma, Rajesh 1974- (IGI Global, 2024)
Demystifying the Dark Side of AI in Business delves into the often-overlooked negative aspects of Artificial Intelligence (AI) and its implications for organizations. In an era where AI is rapidly transforming industries and work environments, it is crucial to understand the potential risks and challenges associated with its implementation. Drawing from a wide range of global perspectives, this book brings together articles from leading researchers, academicians, and professionals across disciplines to shed light on the dark side of AI. Through academic rigor and meticulous analysis, the book addresses key topics such as unethical AI implementation, safety risks, negative social impacts, unintended consequences, and legal concerns surrounding AI adoption.This book covers crucial topics such as governance, ethical concerns, safety risks, social impacts, and future perspectives. By illuminating the negative implications of AI, this book paves the way for responsible and informed AI adoption, ensuring a balance between the potential benefits and the inherent risks associated with this transformative technology. Targeting researchers, academicians, professionals, and students with a wide range of interests, this book offers a rich understanding of the theoretical and practical implications of AI. It serves as a valuable resource for management disciplines like human resource management, marketing, financial management, and operations management, enabling readers to grasp the nuances of ai in different organizational contexts.
Keywords: Artificial intelligence -- Moral and ethical aspects; Information technology -- Economic aspects; Technological innovations -- Economic aspects